Konsep Pendidikan Karakter dalam Perspektif Al-Ghazali dan Relevansinya terhadap Pendidikan Modern - Guntur Febri Tinanto; Burhan Abdullah; Ahmad fahrur rizal; Benny Prasetia (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
This study examines the concept of character education from the perspective of Al-Ghazali and analyzes its relevance to modern educational paradigms. The research is based on a qualitative library approach, utilizing primary sources from Ihya’ ‘Ulum al-Din and supported by contemporary scholarly literature. Data were analyzed through content analysis combined with an analytical-comparative approach to identify key concepts and relate them to modern theories such as social-emotional learning and holistic education. The findings reveal that character education in Al-Ghazali’s framework is grounded in the concept of malakah (stable disposition of the soul), which is formed through continuous habituation, self-discipline, and spiritual purification (tazkiyat al-nafs). Character is not merely external behavior but an internalized moral structure that generates consistent ethical actions. The study also highlights the central role of educators as moral exemplars and emphasizes the inseparable relationship between knowledge and practice. Furthermore, the analysis demonstrates a strong conceptual correspondence between Al-Ghazali’s thought and contemporary educational approaches, particularly in the integration of cognitive, emotional, and spiritual dimensions. This study proposes an integrative framework of character education that bridges classical Islamic ethics and modern pedagogical models. The findings contribute to the development of a holistic and transformative paradigm of education that fosters not only intellectual competence but also moral and existential maturity.